The coaching space: A production of power relationships in organizational settings. (November 2018) - Louis, Dima; Fatien Diochon, Pauline
Given the prevalence of instrumental and positivistic accounts on coaching, our article aims to contribute to a critical theory of coaching by articulating two under-researched topics in the field: power and space. We do so by building on the Lefebvrian political approach to space; more specifically, we show that depending on the coach's experience of the coaching space, three types of power relationships are produced within the coach–coachee–organization triad: independent, mediated, and parallel. Accordingly, the coaching space appears to be either a generator, supporter, or analyzer of power. Overall, by approaching coaching as a political space, we call for increased awareness of the conditions that facilitate the experience of the coaching space as empowering rather than limiting and controlling.